2007
DOI: 10.1111/j.1600-051x.2007.01078.x
|View full text |Cite
|
Sign up to set email alerts
|

Gingival crevicular fluid and serum leptin: their relationship to periodontal health and disease

Abstract: These results suggest that greater the periodontal destruction, lesser is the GCF leptin concentration and greater the serum leptin concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
114
3
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(143 citation statements)
references
References 35 publications
(49 reference statements)
22
114
3
4
Order By: Relevance
“…Torpy et al, [25] stated that during sepsis, a negative correlation between leptin concentration and patient survival was found, a similar state as seen within gingival tissues in periodontal disease progression. Studies reporting the leptin concentrations within gingiva carried out by Johnson and Serio [26], who studied the leptin concentrations within healthy and diseased gingiva using solubilized gingival biopsies; and Karthikeyan and Pradeep [1,14] who assessed the leptin levels within GCF as well as serum; showed results in concordance with our study. Increased leptin levels are generally observed during inflammation as a result of the stimulatory effect of lipopolysaccharide (LPS), and other cytokines such as tumour necrosis factor-α (TNF-α) and interleukin-1α (IL1-α) on leptin production by acting on adipocytes.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Torpy et al, [25] stated that during sepsis, a negative correlation between leptin concentration and patient survival was found, a similar state as seen within gingival tissues in periodontal disease progression. Studies reporting the leptin concentrations within gingiva carried out by Johnson and Serio [26], who studied the leptin concentrations within healthy and diseased gingiva using solubilized gingival biopsies; and Karthikeyan and Pradeep [1,14] who assessed the leptin levels within GCF as well as serum; showed results in concordance with our study. Increased leptin levels are generally observed during inflammation as a result of the stimulatory effect of lipopolysaccharide (LPS), and other cytokines such as tumour necrosis factor-α (TNF-α) and interleukin-1α (IL1-α) on leptin production by acting on adipocytes.…”
Section: Discussionsupporting
confidence: 88%
“…After the discovery of leptin within healthy and inflamed gingiva was confirmed, further studies have since observed that the varying levels of leptin activity within the GCF may play an important role in the periodontal disease cascade. Karthikeyan BV et al, [14] reported that leptin levels decreased progressively in GCF but increased in serum as the periodontal disease progressed. However, further studies are needed to demystify this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Adipocytes in the obese people produce a large quantity of biologically active molecules, such as leptin, and high leptin concentration in blood has been suggested as a risk factor for the cardiovascular diseases. According to Preadeep AR et al (2007), 19 the uses of the laptin are as follows:…”
Section: Discussionmentioning
confidence: 99%
“…Leptin is also involved in two different bone controlling mechanism either by producing direct stimulatory effect on bone growth like osteoblast proliferation, differentiation and prolonging the life span of osteoblasts by inhibiting apoptosis or producing indirect suppressive effect on bone through hypothalamus. Karthikeyan and Pradeep AR have shown that leptin is present in healthy gingiva and leptin concentration reduced coincident to severity of inflammation [8]. The same author also reported that serum leptin levels are increased in periodontitis [9].…”
Section: Adipokines -Key Player In Obesity and Periodontal Diseasementioning
confidence: 93%